PENGARUH TAYANGAN TELEVISI DI RUMAH TERHADAP AKHLAK ANAK USIA 5-6 TAHUN DI TAMAN KANAK-KANAK PKK DESA DALAM KAUM SAMBAS TAHUN PELAJARAN 2019/2020 - Resha Agustia (Jurnal Salome : Multidisipliner Keilmuan, 2023)
This research uses quantitative. This type of research is associative. The population in this study amounted to 72. With a sample of 30 children. for the validity test, 10 children were taken. Data collection tools using indirect communication techniques, observation and validity and reliability tests. The results were tested by testing the validity and reliability as a prerequisite test. The data analysis technique was calculated using IBM SPSS Statistics Ver.24. The 1st and 2nd sub-problems were answered using a simple regression test while the 3rd sub-problem was answered using the one-sample Kolmogorov-Smirnov Test. Based on the results of the SPSS analysis, the sig value in the Annova table is 0.900 70.05 meaning that Ho is accepted and Ha is rejected. It means that there is no significant influence between television shows on children's morals. The relationship between variable television shows (X) on variable children's morals (Y). shown by the model summary table with an R of: 0.24 or 2.4% are in the "Very low" category. Whether the combination of the X variable against the Y variable can be seen in the R Square value in the Summary table, which is 0.001 or 0.1%, while 99.9% is influenced by other factors. The regression equation is Y = 45.405-0.035 X. This means that if the value is 0, the child's morals are 45.405, but if the value of television shows increases by one, the children's morals will decrease by 0.035 every one unit. So based on the regression equation television shows have a negative effect on children's morals.